FvBck1, a component of cell wall integrity MAP kinase pathway, is required for virulence and oxidative stress response in sugarcane Pokkah Boeng pathogen - Zhang, Chengkang; Wang, Jianqiang; Tao, Hong; Dang, Xie; Wang, Yang; Chen, Miaoping; Zhai, Zhenzhen; Yu, Wenying; Xu, Liping; Shim, Won-Bo; Lu, Guodong; Wang, Zonghua (Frontiers in Microbiology, 2015)
Fusarium verticillioides (formerly F. moniliforme) is suggested as one of the causal agents of Pokkah Boeng, a serious disease of sugarcane worldwide. Currently, detailed molecular and physiological mechanism of pathogenesis is unknown. In this study, we focused on cell wall integrity MAPK pathway as one of the potential signaling mechanisms associated with Pokkah Boeng pathogenesis. We identified FvBCK1 gene that encodes a MAP kinase kinase kinase homolog and determined that it is not only required for growth, micro- and macro-conidia production, and cell wall integrity but also for response to osmotic and oxidative stresses. The deletion of FvBCK1 caused a significant reduction in virulence and FB1 production, a possibly carcinogenic mycotoxin produced by the fungus. Moreover, we found the expression levels of three genes, which are known to be involved in superoxide scavenging, were down regulated in the mutant. We hypothesized that the loss of superoxide scavenging capacity was one of the reasons for reduced virulence, but overexpression of catalase or peroxidase gene failed to restore the virulence defect in the deletion mutant. When we introduced Magnaporthe oryzae MCK1 into the FvBck1 deletion mutant, while certain phenotypes were restored, the complemented strain failed to gain full virulence. In summary, FvBck1 plays a diverse role in F. verticillioides, and detailed investigation of downstream signaling pathways will lead to a better understanding of how this MAPK pathway regulates Pokkah Boeng on sugarcane.